2017
DOI: 10.1016/j.eururo.2016.08.055
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Site-specific Recurrence Following Primary Radiation Therapy for Prostate Cancer Using C-11 Choline Positron Emission Tomography/Computed Tomography: A Nomogram for Predicting Extrapelvic Disease

Abstract: Background Management of recurrent prostate cancer (CaP) after radiotherapy (RT) is dependent on accurate localization of the site of recurrent disease. Objective To describe the anatomic patterns and clinical features associated with CaP recurrence following RT identified on advanced imaging. Design, setting, and participants Retrospective review of 184 patients with a rising prostate-specific antigen (PSA) after RT for CaP. Intervention C-11 choline positron emission tomography/computed tomography (Cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 27 publications
(38 reference statements)
5
31
0
Order By: Relevance
“…In the present study, we showed that three out of four relapses were low‐volume and potentially amenable to LAT. These results corroborate the findings of other series showing a similar pattern (Table ) . With regard to the location of recurrences, the dominant pattern is lymphotropic in all reported series (Table ), with bone metastases observed in approximately one in five patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, we showed that three out of four relapses were low‐volume and potentially amenable to LAT. These results corroborate the findings of other series showing a similar pattern (Table ) . With regard to the location of recurrences, the dominant pattern is lymphotropic in all reported series (Table ), with bone metastases observed in approximately one in five patients.…”
Section: Discussionsupporting
confidence: 91%
“…Sobol et al 21 Parker et al 20 PET, positron-emission tomography. *In six patients, the primary treatment method was not registered and those patients are not shown in the frequently, even for patients not entered in the trial.…”
Section: Characteristicmentioning
confidence: 99%
“…Other institutions have shown a limited sensitivity of CholPET when the PSA is <2.0ng/mL (37), which may reflect the lower doses of C-11 choline used in other series relative to the protocol employed here. Indeed, reports from our institution where operative characteristics are available have shown a detection rate of 64% among patients with a PSA <2.0ng/mL (34), compared to 45% as reported in the aforementioned study of 4,000 restaging scans (27). …”
Section: Discussionmentioning
confidence: 72%
“…Previous investigations have established the role for CholPET in the evaluation of biochemical recurrence after either RP or RT (24, 27, 34). The National Comprehensive Cancer Network (NCCN) and the European Association of Urology (EAU) (35, 36) recognize the use of CholPET in the identification of sites of metastatic disease, but acknowledge that additional study is needed to define best practices.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 161 patients with PSA increasing after primary RT who underwent C-11 choline PET/CT, 87% were found to have sites of recurrence, 59% of which were histologically confirmed. 72 The median PSA level of the cohort was 7.8 ng/mL, but with PSA levels less than the Phoenix criteria threshold median of 1.9 ng/mL, 73 71% had confirmed sites of recurrence.…”
Section: Clinically Available Pet Imaging Agents For Recurrent Pcamentioning
confidence: 85%